The Influence of Mindfulness On Students Psychological Well-Being - Unaisyah Kultsum Lasyena; Cinthya Fadillah; Salsabilla Rahma Octavia; Vanis Adellia; Muhammad Naufal Luthfi (CV. Doki Course and Training, 2024)
The purpose of this research is to find out whether there is an effect of Mindfulness on a person's psychological well-being. The research was conducted on students of UIN Raden Fatah Palembang. This research method is quantitative type of regression. Respondents resulting from the survey amounted to 55 respondents. Data collection techniques were carried out by online surveys via Google Forms, using 2 scales namely FFMQ-15: 15 items Five-Facet Mindfulness Questionnaire and Psychological well being scale. The data analysis method for testing the hypothesis uses a simple linear regression method with significant data results of 0.025 <0.05, which means that there is an influence of mindfulness on one's psychological well-being.